Wildfire risk management in the District of Vila Real (Portugal). Issue 3 (4th November 2021) - Rodrigues, André; Raposo, Jorge; Reis, Johnny; Sousa, Miguel; Graça, Daniel; Hermenegildo, Carlos
Abstract : Portugal is a country that is often affected by large wildfires, which can be characterised by a high level of destruction of material goods and deaths. Portugal will never forget the fatalities linked to forest fires in recent years; in 2017, more than 100 people died. Vila Real is one of the districts with the highest occurrence of wildfires. This study characterised the risk of fire for the District of Vila Real, based on Geographic Information Systems. This work applies a methodology at a district level that allows better decision making by those responsible for district civil protection, since they have a new decision making support tool. This new tool gives information about the wildfire risk, the priority of surveillance of the most dangerous areas and the travel time of the firefighters in their emergency response area. Most of the district (61.78%) presents a medium, high or very high risk in the context of wildfires. Regarding travel time, most of the territory under study is more than 15 min from the fire brigades. Since 70% of the district's area is not visible from any lookout post or only from one, the areas in need of enhanced surveillance were determined.